2013
DOI: 10.1111/ahg.12025
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype versus Genotype Methods for Copy Number Variant Analysis of Glutathione S-Transferases M1

Abstract: SummarySeveral variants have been identified for genes encoding Glutathione S-transferase (GST) enzymes; some are associated with significant alteration of protein function. One of the most extensively studied is a copy number variant (CNV) in the GSTM1 gene. In this study, we compared phenotype (positive, null) and genotype (1/1, 1/0, 0/0) methods in order to assess dissimilarities obtained using these two different approaches to evaluate possible methodology-related bias. We analyzed a sample of 1947 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…GSTM1 , GSTP1 , and GSTT1 have been deeply investigated as candidate genes involved in the predisposition to pathologic conditions. In particular, a number of studies have analyzed GSTM1 and GSTT1 deletion polymorphisms that are associated with null phenotypes (i.e., GSTM1 positive/null, GSTT1 positive/null), and two GSTP1 nonsynonymous changes (i.e., GSTP1*I105V and GSTP1*A114V), as these genetic variants may affect drug response and metabolic processes (Bolt and Thier, ; Higgins and Hayes, ; Piacentini et al, ). Besides the putative role those variants play with respect to health‐related traits, some studies have investigated their distribution among human populations (Piacentini et al, ; Polimanti et al, ) in order to provide information about the global distribution of these markers and to furnish reference data for genetic association studies.…”
Section: Discussionmentioning
confidence: 99%
“…GSTM1 , GSTP1 , and GSTT1 have been deeply investigated as candidate genes involved in the predisposition to pathologic conditions. In particular, a number of studies have analyzed GSTM1 and GSTT1 deletion polymorphisms that are associated with null phenotypes (i.e., GSTM1 positive/null, GSTT1 positive/null), and two GSTP1 nonsynonymous changes (i.e., GSTP1*I105V and GSTP1*A114V), as these genetic variants may affect drug response and metabolic processes (Bolt and Thier, ; Higgins and Hayes, ; Piacentini et al, ). Besides the putative role those variants play with respect to health‐related traits, some studies have investigated their distribution among human populations (Piacentini et al, ; Polimanti et al, ) in order to provide information about the global distribution of these markers and to furnish reference data for genetic association studies.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied hGSTM1 polymorphism is a gene deletion whose frequency ranges from 50 to 78% among ethnic groups (Moyer et al 2007). Other studies show functionally significant polymorphisms in hGSTM1 that may be associated with responses to chemotherapy (Moyer et al 2007;Ag undez and Ladero 2008;Piacentini et al 2013). The hGSTM1/hGSTT1 double-null genotype is associated with poor treatment outcome in acute myeloid leukemia and with increased risk of drug-induced liver injury (Lucena et al 2008;Xiao et al 2014).…”
Section: Tissue and Species Distributionmentioning
confidence: 99%
“…GSTM1 and GSTM5 have been localized within the NSR and RPE/choroid of the human eye, and both genes had reduced mRNA and protein in AMD eyes (without null genotype 0/0) in the same pan-retinal studies (15). Piacentini et al analysis of GSTM1 polymorphisms have recently emphasized the importance of using genotype association (+/+, +/0, 0/0) over phenotype (present, null) when looking at GSTM1 protein function (32). Oz et al performed phenotype analysis with PCR of peripheral blood leukocytes for GSTM1 , GSTT1 and GSTP1 in exudative AMD vs. controls and found that paired homozygous deletions for GSTM1 / GSTT1 or GSTM1 / GSTP1 increase AMD risk (33).…”
Section: Discussionmentioning
confidence: 99%